Supply Chain Collaboration and its relevant factors’ contribution to OEM - Ji, Wenjing (2010)
Supply chain has become a key business issue for many companies and it is based on the integration of all activities that add value to customers, from product design through to delivery. Building an effective and efficient manufacturing supply chain can become a core or even a distinctive competency. However, building a close relationship with suppliers is not easy, and it would require companies develop high level of trust, appropriate communication, enhanced information technology, proper cross-functional coordination, and many other aspects which are not involved in this project due to the length of this dissertation and the time for doing it. This dissertation is go to firstly explain the relevant theories of supply chain, such as relevant factors which effect on supply chain collaboration, and analyze the relationship among them. Latterly, it is going to prove this relationship by specific cases and identify how particular factors benefit OEM and the contribution of these factors to successful supply chain collaboration.